Negative-electrode-free lithium metal battery as well as preparation method and application thereof
By using fluorinated amide electrolyte with lithium supplement additives to form a dense thin lithium layer in a negative electrode-free lithium metal battery, the problem of short battery cycle life is solved, and the battery cycle stability is significantly improved while maintaining high energy density. Effect.
Patent Information
- Application Number
- CN202310954543.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The cycle life of negative electrode-free lithium metal batteries is relatively short, mainly due to the irreversible consumption of metal lithium during the formation of solid electrolyte interface film, dendrites and "dead lithium", which leads to insufficient lithium inventory and inability to effectively compensate for irreversible lithium losses.
By combining the new fluorinated amide electrolyte with lithium supplement additives in the internal material system of the battery, a dense thin lithium layer is formed in situ on the negative electrode current collector during the first charge as an additional lithium inventory, compensating for irreversible lithium loss .
The cycle life of negative electrode-free lithium metal batteries is significantly improved, while maintaining high energy density, which hardly affects the energy density and manufacturing cost of the battery.
Smart Images

Figure BDA0004369509310000101 
Figure BDA0004369509310000111 
Figure HDA0004369509340000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode-free lithium batteries, and in particular relates to a high energy density negative electrode-free lithium metal battery and a preparation method and application thereof. Background Art
[0002] The negative electrode-free lithium metal battery structurally eliminates the need for traditional graphite / silicon carbon or excess metallic lithium, avoids the safety risks brought by the use of chemically active lithium metal, saves costs while simplifying the production process, and minimizes the mass and volume of the battery, providing maximum energy density, so that ordinary positive electrodes can also achieve high energy density; in addition, the system does not need to consider the negative electrode capacity / positive electrode capacity ratio (i.e., N / P ratio), and the assembly is completed by the lithiated positive electrode and the negative electrode current collector with inactive substances in a fully discharged state, so the production process is safer and simpler.
[0003] However, although anode-free lithium metal batteries show great advantages and application prospects, metallic lithium still faces severe challenges in the reversibility of electrodeposition / stripping. In particular, when the solid electrolyte interface film (SEI), dendrites and "dead lithium" are formed, the active lithium will inevitably be consumed. Since there is no additional lithium inventory to make up for the irreversible lithium loss, the cycle life of anode-free lithium metal batteries is extremely short, which is difficult to meet the requirements of practical applications.
[0004] Therefore, improving the reversibility of deposition / stripping of metallic lithium on the current collector is a core scientific issue for extending the cycle life of anode-free lithium metal batteries, which requires systematic research at multiple levels from battery materials to battery design. Among them, the optimal design of the electrolyte is one of the most critical parts affecting the cycle performance of anode-free lithium metal batteries. In recent years, the research on some new electrolytes has effectively improved the cycle life of anode-free lithium metal batteries. For example, Yi Cui et al. designed a fluoroether electrolyte (1 mol / L LiFSI in FDMB) to make the capacity retention rate of a 325Wh / kg anode-free soft-pack lithium metal battery (Cu||NCM811) 80% after 70 cycles (Nat.Energy 2020, 5, 526-533). Jun Liu et al. used a local high-concentration electrolyte (1.5 mol / L LiFSI in DME-TTE) to achieve a capacity retention rate of 80% for a 350Wh / kg negative electrode-free soft-pack lithium metal battery (Cu||NCM622) after 100 cycles (Nat. Energy 2021, 6, 723-732).
[0005] Another idea to improve the cycle life of anode-free lithium metal batteries is to use a lithium compensation scheme from the positive electrode side, that is, to alleviate the life attenuation of anode-free lithium metal batteries by adding additional lithium sources. For example, in the use of conventional lithium supplement additives, Shengshui Zhang et al. added 10wt.% of lithium supplement additive Li2CuO2 on the positive electrode side to make the anode-free lithium metal battery retain 80% of the capacity retention rate after 50 cycles (Electrochem. Commun. 2018, 89, 23–26). Bing Joe Hwang et al. added 20wt.% of lithium supplement additive lithium oxalate (Li2C2O4) on the positive electrode side to make the anode-free lithium metal battery retain 80% of the capacity retention rate after 50 cycles (ACS Appl. Mater. Interfaces 2022, 14, 23, 26724–26732). Obviously, even if the conventional lithium supplement additive is added in an amount of 20wt.%, the improvement in the cycle life of anode-free lithium metal is not significant. In terms of special lithium replenishment methods, Liumin Suo et al. reported a lithium-rich Li2[Ni 0.8 Co 0.1 Mn 0.1]O2 (Li2NCM811) positive electrode. The lithium source stored in the Li2NCM811 positive electrode is nearly twice that of ordinary NCM811. Combined with a high-concentration electrolyte (6mol / L LiFSI in DME), the capacity retention rate of a 0.060Ah single-layer negative electrode-free soft-pack lithium metal battery can be increased from 38% to 84% after 100 cycles (Angew. Chem. Int. Ed. 2021, 60, 8289–8296). However, the preparation of this lithium-rich positive electrode material requires the use of NCM811 and highly dangerous n-butyl lithium to react in an inert atmosphere, which increases the difficulty and actual cost of large-scale preparation, and the energy density of the small-capacity single-layer battery cell structure is <300Wh / kg, and practical applications are still challenging. Haoshen Zhou et al. added 18.2wt.% of lithium oxide as a lithium supplement additive on the positive electrode side (of which the positive electrode active material accounts for only 71%), and combined it with a double salt ether-based electrolyte containing HFE additives (1mol / L LiTFSI+1.5mol / L LiFSI in G3-HFE), so that the additional lithium source generated by the decomposition of Li2O was retained on the Cu current collector during the first charge, thereby making the 320Wh / kg, 2.46Ah negative electrode-free soft-pack lithium metal battery cycle 300 times with a capacity retention rate of 80% (Nat.Energy 2021,6,653–662). However, this system produces a large amount of oxygen, which can react exothermically with the fresh metal lithium deposited on the negative electrode, increasing the danger. At the same time, the use of a large amount of Li2O reduces the energy density of the battery, which inevitably undermines the advantages of negative electrode-free lithium metal batteries in safety and energy density.
[0006] Therefore, without affecting the energy density, manufacturing cost and large-scale production requirements, improving the cycle life of negative electrode-free lithium metal batteries by further optimizing the internal material system of the battery is a key challenge that needs to be urgently addressed. Summary of the invention
[0007] Starting from the design of the internal material system of the battery, the inventors combined a new fluorinated amide electrolyte with a lithium supplement additive, so that the negative electrode-free lithium metal battery can form a thin lithium layer with a dense deposition structure in situ on the negative electrode current collector during the first charge, which serves as additional lithium inventory to make up for the irreversible lithium loss, thereby significantly improving the cycle life of the negative electrode-free lithium metal battery while maintaining a high energy density.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] One aspect of the present invention provides a negative electrode-free lithium metal battery.
[0010] Another aspect of the present invention provides a method for preparing the negative electrode-free lithium metal battery.
[0011] Another aspect of the present invention provides use of the negative electrode-free lithium metal battery in electronic devices, smart grids or electric vehicles.
[0012] According to one aspect of the present invention, there is provided a negative electrode-free lithium metal battery, comprising:
[0013] A positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer containing a lithium supplement additive;
[0014] Anode current collector;
[0015] An electrolyte comprising at least one boron-containing lithium salt and a fluorinated amide compound solvent; and
[0016] Diaphragm.
[0017] 1. Positive electrode
[0018] In the present invention, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector.
[0019] There is no particular limitation on the positive electrode current collector, which can be a positive electrode current collector conventionally used for lithium batteries, including a metal current collector, such as one selected from aluminum, titanium, nickel and iron or an alloy thereof, preferably aluminum foil; a non-metallic current collector, such as one or more selected from carbon fiber cloth, carbon fiber paper, graphite paper, and conductive organic polymers, preferably carbon fiber paper; a metal-polymer composite current collector, such as having a three-layer structure, the middle layer is a polymer film, and the upper and lower layers are metal coatings, wherein the polymer can be one or more of polycarbonate, polystyrene, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polypropylene, polyethylene, polyvinylidene chloride, polybenzimidazole, ethylene-vinyl acetate copolymer, polyimide, polyimide-triphenyl phosphate copolymer and polyurethane, preferably a polyimide-triphenyl phosphate copolymer with flame retardant properties. The positive electrode current collector is preferably a composite current collector of aluminum and polyimide-triphenyl phosphate copolymer, such as an aluminum-plated composite current collector of polyimide-triphenyl phosphate copolymer. The composite current collector can effectively enhance the safety performance of the battery, reduce the cost of raw materials, and increase the energy density of the battery. The thickness of the positive electrode current collector can be 1-100 μm, preferably 1-20 μm.
[0020] The positive electrode active material layer of the present invention comprises a positive electrode active material and a lithium supplement additive. In addition, the positive electrode active material layer may also comprise: a conductive material for enabling electrons to move smoothly in the positive electrode, a binder for increasing the bonding force between the positive electrode active materials or between the positive electrode active material and the positive electrode current collector, the positive electrode active material and the lithium supplement additive.
[0021] There is no particular limitation on the positive electrode active material, and it can be a positive electrode active material conventionally used in lithium batteries, including ternary nickel cobalt manganese oxide positive electrode materials, such as Li[Ni 0.5 Mn 0.2 Co 0.3 ]O2(NCM523), Li[Ni 0.6 Mn 0.2 Co 0.2 ]O2(NCM622), Li[Ni 0.8 Mn 0.1 Co 0.1 ]O2(NCM811), Li[Ni 0.9 Mn 0.05 Co 0.05 ]O2 (NCM955), lithium-rich manganese-based positive electrode material (LMR), lithium nickel manganese oxygen positive electrode material (LNMO), lithium iron phosphate positive electrode material (LiFePO4), lithium manganate positive electrode material (LiMn2O4), lithium iron manganese phosphate positive electrode material (LMFP), lithium cobalt oxide positive electrode material (LiCoO2), lithium sulfide positive electrode material (Li2S) or more, but not limited thereto. Preferably, the positive electrode adopts ternary nickel cobalt manganese oxide positive electrode material (NCM523, NCM622, NCM811, NCM955) with different nickel contents, especially NCM811.
[0022] Based on the total weight of the positive electrode active material layer, the positive electrode active material may be contained in an amount of 80 wt % to 99 wt %. If the amount of the positive electrode active material is less than the range, the energy density of the battery will be reduced. If the amount of the positive electrode active material exceeds the range, the content of the lithium supplement additive is too small, resulting in an insignificant effect on the improvement of the battery cycle life.
[0023] The lithium-supplementing additive is a lithium-containing compound having the ability to release lithium ions and an irreversible capacity of more than 50%, including binary lithium-containing compounds such as Li2O, Li2O2, Li3N, Li2S, Li2C2O4, etc., preferably Li2C2O4; lithium-rich compounds such as Li2Ni 1-x M x O2 (where 0≤x<1, and M is at least one selected from Mn, Fe, Co, Cu, Zn, Mg, Cd), Li5Fe 1- x N x O4 (wherein 0≤x<1, and N is at least one selected from Mn, Ni, Co, Cu, Zn, Mg, Cd), etc., preferably the lithium supplement additive is one or two of Li2NiO2 and Li5FeO4.
[0024] Based on the total weight of the positive electrode active material layer, the lithium supplement additive may be contained in an amount of 0.5 wt % to 20 wt %, preferably 2 wt % to 10 wt %. Similarly, if the amount of the lithium supplement additive is less than the range, the effect of improving the battery cycle life will not be obvious. If the amount of the lithium supplement additive exceeds the range, not only the energy density will be compromised, but other battery properties may also deteriorate, such as cycle life, power, safety performance, etc.
[0025] In addition, the conductive material can be a carbon material such as carbon black, acetylene black, Ketjen black, carbon nanotubes; or a conductive polymer such as polyaniline, polythiophene, polyacetylene and polypyrrole. Based on the total weight of the positive electrode active material layer, the conductive material can be contained in an amount of 0.1 wt% to 5 wt%.
[0026] In addition, the binder may be polyvinyl acetate, polyvinyl alcohol, polyethylene oxide, polyvinyl pyrrolidone, alkylated polyethylene oxide, cross-linked polyethylene oxide, polyvinyl ether, polymethyl methacrylate, polyvinylidene fluoride, polyhexafluoropropylene and a copolymer of polyvinylidene fluoride (product name: Kynar), polyethyl acrylate, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinyl pyridine, polystyrene and derivatives, blends and copolymers thereof. Based on the total weight of the positive electrode active material layer, the binder may preferably be contained in an amount of 0.1 wt % to 5 wt %.
[0027] 2. Negative Electrode Current Collector
[0028] In the present invention, the negative electrode current collector does not contain negative electrode active materials, so it is called no negative electrode.
[0029] The negative electrode current collector includes a metal current collector, such as one selected from copper, nickel, cobalt, titanium and iron or an alloy of two or more thereof, preferably copper foil; a non-metallic current collector, such as one or more selected from carbon fiber cloth, carbon fiber paper, graphite paper, conductive organic polymer, etc., preferably graphite paper; a metal-polymer composite current collector, such as having a three-layer structure, the middle layer is a polymer film, the upper and lower layers are metal coatings, wherein the polymer can be selected from polycarbonate, polystyrene, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polypropylene, polyethylene, polyvinylidene chloride, polybenzimidazole, ethylene-vinyl acetate copolymer, polyimide, polyimide-triphenyl phosphate copolymer and polyurethane. One or more, preferably a polyimide-triphenyl phosphate copolymer with flame retardant properties. The negative electrode current collector is preferably a composite current collector of copper and polyimide-triphenyl phosphate copolymer, such as a copper-plated composite current collector of polyimide-triphenyl phosphate. The thickness of the negative electrode current collector may be 1-100 μm, preferably 1-10 μm.
[0030] The present invention also covers a negative electrode current collector with a coating. The function of the negative electrode current collector coating is to promote the dense deposition and growth of lithium metal on its surface and / or inhibit the corrosion of the deposited lithium metal. The coating can be one of the metal-containing indium, cobalt, germanium, aluminum, tin, gold, silver, zinc, magnesium, silicon, bismuth, palladium, platinum or an alloy of two or more thereof, or can be acetylene black, ketjen black, carbon black, graphite, graphene, conductive polymer, artificial interface film (artificial SEI) containing non-metal, or a mixture of the above metal and non-metal combination.
[0031] 3. Electrolyte
[0032] In the present invention, the electrolyte uses boron-containing lithium salt as the main salt (may also contain other salts) and fluorinated amide compounds as the organic solvent. In addition, the electrolyte may also contain functional additives (ie, electrolyte additives) as needed.
[0033] The boron-containing lithium salt can be one or more selected from lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), lithium tetrafluoroborate (LiBF4), lithium fluoroalkoxyborate, lithium fluoroalkoxyfluoroborate, lithium fluoroalkoxybisfluoroborate, and lithium fluoroalkoxytrifluoroborate, preferably lithium difluorooxalatoborate (LiDFOB).
[0034] The fluorinated amide compound can be one or more selected from N,N-dimethyltrifluoroacetamide, N-methoxy-N-methyltrifluoroacetamide, N-methyltrifluoroacetamide, N,N-diethyltrifluoroacetamide, N-(trifluoromethanesulfonyl)trifluoroacetamide, N,O-bis(trimethylsilyl)trifluoroacetamide, N-methyl-N-(trimethylsilyl)trifluoroacetamide, bis(trimethylsilyl)trifluoroacetamide, N-methyltrimethylsilyltrifluoroacetamide, N-methylbis(trifluoroacetyl)amide, trifluoroacetamide, and bistrifluoroacetamide, preferably N,N-dimethyltrifluoroacetamide.
[0035] Based on the total weight of the electrolyte, it can contain 5 wt% to 50 wt% (e.g., 10 wt% to 35 wt%) of boron-containing lithium salt. If the content of lithium salt is less than 5 wt%, the ionic conductivity of the electrolyte will be reduced, affecting the deposition effect of metallic lithium. If the content of lithium salt exceeds 50 wt%, the cost and viscosity of the electrolyte will be increased, and the wettability to the electrode and the diaphragm will be reduced.
[0036] In some embodiments, the electrolyte comprises lithium difluorooxalatoborate (LiDFOB) and N,N-dimethyltrifluoroacetamide, and the molar ratio of lithium difluorooxalatoborate (LiDFOB) to N,N-dimethyltrifluoroacetamide is 1:5.
[0037] The functional additive may be a salt or an organic solvent, such as tris(2,2,2-trifluoroethyl)phosphite (TTFEP), 1,3,6-hexanetrinitrile (HTCN), fluorotoluene (FB), tris(trimethylsilyl)borate (TMSB), tris(trimethylsilyl)phosphate (TMSP), tris(trimethylsilyl)phosphite (TMSPi), hexamethyldisilazane (HMDS), 1,3-propylene sultone (PRS), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFE) C), bis(2,2,2-trifluoroethyl) carbonate (TFEC), fluoroethyl methyl carbonate (FEMC), vinylene carbonate (VC), propylene sulfite (PS), trifluoromethyl vinyl carbonate (TFPC), vinyl sulfate (DTD), vinyl sulfite (ES), lithium difluorophosphate (LiDFP), lithium difluorobisoxalate phosphate (LiDODFP), lithium tetrafluorooxalate phosphate (LiTFOP), lithium nitrate (LiNO3), lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiCl O4), lithium trifluoromethanesulfonate (LiOTf), lithium bis(fluorosulfonyl imide) (LiFSI), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), one or more thereof.
[0038] The functional additives can be added by those skilled in the art according to the desired functions and the appropriate amount can be determined. For example, based on the total weight of the electrolyte, the functional additives can be contained in an amount of 0.1 wt % to 10 wt %, preferably 0.5 wt % to 5 wt %.
[0039] 4. Diaphragm
[0040] In the present invention, the diaphragm is a physical diaphragm having the function of physically separating electrodes, and can be used without particular restriction, as long as it is used as a diaphragm in a conventional lithium secondary battery, and in particular, a diaphragm having low resistance to ion migration in an electrolyte and having excellent electrolyte impregnation ability is preferred. Specifically, the diaphragm can be a porous polymer film, for example, a porous polymer film made of one of a polyolefin polymer such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer, or a composite porous polymer film made of two or more, which can be used alone or in the form of its laminate, or can be a porous non-woven fabric, for example, a non-woven fabric made of glass fiber with a high melting point, polyethylene terephthalate fiber, etc. The diaphragm can contain a surface functional coating material, such as a ceramic coating, a solid electrolyte coating or a composite coating of two or more, but is not limited thereto. The ceramic may include: aluminum oxide (Al2O3), magnesium oxide (MgO), titanium dioxide (TiO2), zirconium dioxide (ZrO2), silicon dioxide (SiO2), barium titanate (BaTiO3), etc.; the solid electrolyte may include: lithium phosphorus oxynitride (LiPON), lithium zinc germanate (LISICON), lithium germanium phosphosulfur (LGPS), lithium phosphorus sulfur chlorine (LPSCl), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), halide solid electrolyte (Li x MCl6, M is a metal element), polyethylene oxide (PEO), polysiloxane (PS), polypropylene carbonate (PPC), polyacrylonitrile (PAN), polyacrylate (PBA), polymethyl methacrylate (PMMA) and polyvinylidene fluoride (PVDF), etc.
[0041] In addition to the positive electrode, negative electrode, separator and electrolyte mentioned above, the battery of the present invention may also include other structures such as a chip, a capacitor, a casing and the like as required.
[0042] The anode-free lithium metal battery according to the present invention is a cathode-free lithium metal battery with high energy density and long cycle life. Here, "high energy density and long cycle life" means that the cathode-free lithium metal battery according to the present invention further significantly improves its cycle life while maintaining or maintaining the high energy density (>350Wh / kg, even >400Wh / kg, >450Wh / kg and >500Wh / kg) of conventional cathode-free lithium metal batteries.
[0043] According to another aspect of the present invention, a method for preparing the negative electrode-free lithium metal battery is provided, comprising the following steps:
[0044] coating the composition for forming the positive electrode active material layer on the positive electrode current collector to thereby prepare the positive electrode;
[0045] Mixing a composition for forming the electrolyte comprising at least one of the boron-containing lithium salt and a fluorinated amide compound solvent to thereby prepare the electrolyte;
[0046] The positive electrode, the negative electrode current collector, the electrolyte and the separator are arranged to thereby prepare the negative electrode-free lithium metal battery.
[0047] The positive electrode can be prepared according to a conventional method, and specifically, a positive electrode active material layer-forming composition prepared by mixing a positive electrode active material, a lithium supplement additive, a conductive material and a binder in an organic solvent or water is coated on a positive electrode current collector, followed by drying and optionally rolling. In this case, the organic solvent can evenly disperse the positive electrode active material, the lithium supplement additive, the binder and the conductive material, and can be easily evaporated. Specifically, N-methylpyrrolidone, dimethylformamide, ethylene glycol dimethyl ether, acetonitrile, etc. can be used as an organic solvent.
[0048] According to another aspect of the present invention, there is provided use of the negative electrode-free lithium metal battery in electronic devices, smart grids or electric vehicles.
[0049] In this document, the terms "include", "including", "have", "contain" or any other similar terms are open conjunctions, which are intended to cover non-exclusive inclusions. For example, a composition or product containing multiple elements is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or product. In addition, unless otherwise explicitly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist). In addition, in this document, the interpretation of the terms "include", "including", "have", and "contain" should be considered to have been specifically disclosed and simultaneously cover closed or semi-closed conjunctions such as "consisting of" and "consisting essentially of".
[0050] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all secondary ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially secondary ranges defined by all integer values, and should be deemed to have specifically disclosed individual values such as 1, 2, 3, 4, 5, 6, 7, 8, etc. within the range. Unless otherwise specified, the above interpretation method applies to all contents of the entire present invention, regardless of whether the range is broad or not.
[0051] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0052] In this document, under the premise of achieving the purpose of the invention, numerical values should be understood to have the accuracy of the number of significant digits of the numerical value. For example, the number 40.0 should be understood to cover the range from 39.50 to 40.49.
[0053] The above embodiments are only exemplary embodiments of the present invention and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.
[0054] Beneficial Effects
[0055] The beneficial effects of the present invention are as follows:
[0056] (1) The present invention combines a fluorinated amide electrolyte with a lithium supplement additive to form a dense thin lithium layer in situ on the negative electrode current collector as a lithium reservoir during the first charging process. The lithium reservoir can compensate for the consumption of active lithium during the cycle process, thereby significantly improving the cycle stability of the negative electrode-free lithium metal battery without affecting the energy density.
[0057] (2) The present invention combines a fluorinated amide electrolyte with a positive electrode lithium supplement additive, and the energy density of the negative electrode-free lithium metal battery is 533Wh kg under practical conditions. -1 The cycle life of the Cu||NCM811 anode-free soft-pack lithium metal battery (100% DoD) reaches 164 times; the energy density is 426Wh kg-1 The cycle life of the Cu||NCM811 negative electrode-free soft-pack lithium metal battery (80% DoD) reaches 486 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The energy density-voltage curve of the first charge and discharge of the negative electrode-free soft-pack lithium metal battery assembled in Comparative Example 4 and Example 1 at room temperature with a voltage window of 2.8 to 4.4V is shown. DETAILED DESCRIPTION
[0059] The present invention will be described in detail below according to the accompanying drawings and preferred embodiments, and the purpose and effect of the present invention will become more clear. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0060] Preparation Example:
[0061] Preparation of negative electrode-free soft-pack lithium metal battery:
[0062] The assembly is carried out in the order of lamination, tab welding, top and side sealing, liquid injection and packaging. The liquid injection and packaging are carried out in a glove box and a vacuum pre-sealing machine is used for packaging.
[0063] Preparation of positive electrode sheet: positive electrode active material, lithium supplement additive, binder and conductive agent are made into slurry, coated on both sides of 12μm thick aluminum foil, and cut to size. The above materials are purchased from Shenzhen Kejing.
[0064] The negative electrode current collector was 4 μm thick copper foil purchased from Shenzhen Kejing;
[0065] The separator was a 12 μm thick polyethylene (PE) separator purchased from Celgard;
[0066] Aluminum tabs, nickel tabs and 113 μm thick aluminum-plastic film were purchased from Shenzhen Kejing.
[0067] Preparation of electrolyte:
[0068] The local high concentration electrolyte is prepared by lithium bis(fluorosulfonyl)imide (LiFSI) with a molar ratio of 1.0:1.2:3.0:ethylene glycol dimethyl ether (DME):1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE). Specifically, 1.50g of lithium bis(fluorosulfonyl)imide (LiFSI) is dissolved in 1.0mL of ethylene glycol dimethyl ether (DME) solvent to obtain a high concentration electrolyte. Then, 1.0mL of the high concentration electrolyte is mixed with 1.93mL of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) solvent to obtain a local high concentration electrolyte, in which the mass proportion of lithium salt is 19.0wt%. This local high concentration electrolyte is the local high concentration electrolyte with the best performance reported so far.
[0069] The fluorinated amide electrolyte is prepared from lithium difluorooxalate borate (LiDFOB) and N,N-dimethyltrifluoroacetamide in a molar ratio of 1:5. Specifically, 0.25 g of lithium difluorooxalate borate (LiDFOB) is dissolved in 1.0 mL of N,N-dimethyltrifluoroacetamide solvent to obtain a fluorinated amide electrolyte, in which the mass proportion of lithium salt is 17.2 wt%.
[0070] Constant current charge and discharge test of non-negative soft-pack lithium metal battery: The test is conducted at a constant current within a set voltage range using the Xinwei battery test system; the non-negative soft-pack lithium metal battery is placed in a fixture with a pressure of 200kPa for testing. The cycle life of the battery is defined as 80% capacity retention based on the initial discharge capacity at 0.2C.
[0071] Example 1
[0072] The positive electrode is a 12 μm thick aluminum foil coated on both sides with high nickel ternary positive electrode nickel cobalt manganese oxide Li[Ni 0.8 Mn 0.1 Co 0.1 ]O2 (NCM811) positive electrode material layer, composed of 90.0wt.% NCM811 as positive electrode active material, 7.5wt.% Li2NiO2 as lithium supplement additive, 1.0wt.% multi-walled carbon nanotubes as conductive agent, and 1.5wt.% polyvinylidene fluoride (PVDF) as binder, with a single-sided coating surface density of 26.5mg / cm 2 ; The negative electrode is a 4μm thick copper foil current collector with no active material; the diaphragm is a 12μm thick polyethylene (PE) diaphragm; the injection and packaging are performed in a glove box and packaged using a vacuum pre-sealing machine. The electrolyte uses the fluorinated amide electrolyte prepared above, in which the mass proportion of lithium salt is 17.2wt%. The electrolyte injection amount of the soft-pack battery is 1.5g / Ah. The capacity of the negative-electrode-free soft-pack lithium metal battery is 2.62Ah, and the corresponding energy density is 533Wh / kg.
[0073] Electrochemical performance test method: At a temperature of 25°C, the voltage range is set at 2.8-4.4V (100% DoD), and after 2 cycles at a charge and discharge rate of 0.1C, a long-term charge and discharge cycle is performed at a charge rate of 0.2C and a discharge rate of 0.5C.
[0074] Example 2
[0075] The preparation method of the negative electrode-free soft-pack lithium metal battery is consistent with that in Example 1.
[0076] The electrochemical test method is different from that of Example 1 in that the voltage range is set at 3.6-4.3 V (80% DoD).
[0077] Example 3
[0078] The positive electrode is a 12μm thick aluminum foil coated with lithium manganese iron phosphate LiMn on both sides. 0.6 Fe 0.4 The PO4 (LMFP) positive electrode material layer is composed of 90.0wt.% LMFP as a positive electrode active material, 5.0wt.% Li5FeO4 as a lithium supplement additive, 1.5wt.% multi-walled carbon nanotubes as a conductive agent, and 3.5wt.% polyvinylidene fluoride (PVDF) as a binder. The single-sided coating surface density is 17.5mg / cm 2 ; The negative electrode is a 4μm thick copper foil current collector with no active material; the diaphragm is a 12μm thick polyethylene (PE) diaphragm; the injection and packaging are performed in a glove box and packaged using a vacuum pre-sealing machine. The electrolyte uses the fluorinated amide electrolyte prepared above, in which the mass proportion of lithium salt is 17.2wt%. The electrolyte injection amount of the soft-pack battery is 1.5g / Ah. The capacity of the negative-electrode-free soft-pack lithium metal battery is 2.37Ah, and the corresponding energy density is 370Wh / kg.
[0079] Electrochemical performance test method: At a temperature of 25°C, the voltage range is set at 3.0-4.4V (100% DoD), and after 2 cycles at a charge and discharge rate of 0.1C, a long-term charge and discharge cycle is performed at a charge rate of 0.2C and a discharge rate of 0.5C.
[0080] Comparative Example 1
[0081] The positive electrode is a 12 μm thick aluminum foil coated on both sides with high nickel ternary positive electrode nickel cobalt manganese oxide Li[Ni 0.8 Mn 0.1 Co 0.1]O2 (NCM811) positive electrode material layer, composed of 97.5wt.% NCM811 as positive electrode active material, 1.0wt.% multi-walled carbon nanotubes as conductive agent, and 1.5wt.% polyvinylidene fluoride (PVDF) as binder, with a single-sided coating surface density of 26.5mg / cm 2 ; The negative electrode is a 4μm thick copper foil current collector with no active material; the diaphragm is a 12μm thick polyethylene (PE) diaphragm; the injection and packaging are performed in a glove box and packaged using a vacuum pre-sealing machine. The electrolyte uses the local high-concentration electrolyte prepared above, in which the mass proportion of lithium salt is 19.0wt%. The electrolyte injection amount of the soft-pack battery is 1.5g / Ah. The capacity of the negative-electrode-free soft-pack lithium metal battery is 2.7Ah, and the corresponding energy density is 549Wh / kg.
[0082] The electrochemical test method is consistent with that in Example 1.
[0083] Comparative Example 2
[0084] The preparation method of the negative electrode-free soft-pack lithium metal battery is different from that of Example 1 in that the electrolyte is replaced with the local high-concentration electrolyte prepared above.
[0085] The electrochemical test method is consistent with that in Example 1.
[0086] Comparative Example 3
[0087] The preparation method of the negative electrode-free soft-pack lithium metal battery is consistent with that of Comparative Example 2.
[0088] The electrochemical test method is consistent with that of Example 1, except that the voltage range is set at 3.6-4.3 V (80% DoD).
[0089] Comparative Example 4
[0090] The preparation method of the negative electrode-free soft-pack lithium metal battery is different from that of Comparative Example 1 in that the electrolyte is replaced with the fluorinated amide electrolyte prepared above.
[0091] The electrochemical test method is consistent with that in Example 1.
[0092] Comparative Example 5
[0093] The positive electrode is a 12μm thick aluminum foil coated with lithium manganese iron phosphate positive electrode LiMn 0.6 Fe 0.4 The PO4 (LMFP) positive electrode material layer is composed of 95.0wt.% LMFP as a positive electrode active material, 1.5wt.% multi-walled carbon nanotubes as a conductive agent, and 3.5wt.% polyvinylidene fluoride (PVDF) as a binder. The single-sided coating surface density is 17.5mg / cm 2The negative electrode is a 4μm thick copper foil current collector without active material; the diaphragm is a 12μm thick polyethylene (PE) diaphragm; the injection and packaging are performed in a glove box and the packaging is performed using a vacuum pre-sealing machine. The electrolyte uses the local high-concentration electrolyte prepared above, and the electrolyte injection amount of the soft-pack battery is 1.5g / Ah. The capacity of the negative-electrode-free soft-pack lithium metal battery is 2.4Ah, and the corresponding energy density is 377Wh / kg.
[0094] The electrochemical test method is consistent with that of Example 3.
[0095] Comparative Example 6
[0096] The preparation method of the negative electrode-free soft-pack lithium metal battery is different from that of Example 3 in that the electrolyte is replaced with the local high-concentration electrolyte prepared above.
[0097] The electrochemical test method is consistent with that in Example 3.
[0098] Comparative Example 7
[0099] The preparation method of the negative electrode-free soft-pack lithium metal battery is different from that of Comparative Example 5 in that the electrolyte is replaced with the fluorinated amide electrolyte prepared above.
[0100] The electrochemical test method is consistent with that of Example 3.
[0101] The test results of Examples 1-3 and Comparative Examples 1-7 are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] As can be seen from Table 1, for the negative electrode-free soft-pack lithium metal battery based on Li2NiO2 lithium supplement, adding the lithium supplement additive to the negative electrode-free soft-pack lithium metal battery with a local high concentration electrolyte (Comparative Examples 1-2) only increases the cycle life by 43.6%, while adding the lithium supplement additive to the negative electrode-free soft-pack lithium metal battery with a fluorinated amide electrolyte (Example 1) increases the cycle life by 105% compared with Comparative Example 4.
[0106] For the negative electrode-free soft-pack lithium metal battery based on Li5FeO4 lithium supplement, the addition of lithium supplement additives to the negative electrode-free soft-pack lithium metal battery with local high concentration electrolyte (Comparative Examples 5-6) only increased the cycle life by 45.2%, while the addition of lithium supplement additives to the negative electrode-free soft-pack lithium metal battery with fluorinated amide electrolyte (Example 3) increased the cycle life by 93.3% compared with Comparative Example 7. In addition, under the condition of 80% discharge depth, in the comparison of the cycle life of the negative electrode-free soft-pack lithium metal batteries to which lithium supplement additives were added, the cycle life of Example 2 was more than 5 times that of Comparative Example 3, indicating that the synergistic effect of the fluorinated amide electrolyte and the addition of lithium supplement can significantly extend the cycle life of the battery while maintaining the high energy density characteristics of the negative electrode-free soft-pack lithium metal battery.
[0107] Figure 1 The energy density-voltage curves of the negative electrode-free soft-pack lithium metal batteries corresponding to Comparative Example 4 and Example 1 during the first charge and discharge are shown. The reversible efficiency of the first charge of Comparative Example 4 is 93.7%, and the corresponding discharge energy density is 549Wh / kg. Due to the initial irreversibility of the lithium supplement additive in Example 1, the reversible efficiency of the first charge is 86.4%, and the corresponding energy density is 533Wh / kg. Therefore, the energy density of the battery with 7.5% lithium supplement additive is only reduced by 16Wh / kg, and it is still maintained at a level of >500Wh / kg, which hardly affects the high energy density characteristics of the negative electrode-free soft-pack lithium metal battery.
Claims
1. A negative electrode-free lithium metal battery, comprising: A positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer containing a lithium supplement additive; Anode current collector; An electrolyte comprising at least one boron-containing lithium salt and a fluorinated amide compound solvent; and Diaphragm.
2. The negative electrode-free lithium metal battery according to claim 1, wherein: The positive electrode current collector is selected from a metal current collector, a non-metal current collector or a metal-polymer composite current collector; Preferably, the metal current collector is an alloy of one or more selected from aluminum, titanium, nickel and iron, preferably aluminum foil; the non-metallic current collector is one or more selected from carbon fiber cloth, carbon fiber paper, graphite paper and conductive organic polymer, preferably carbon fiber paper; the polymer in the metal-polymer composite current collector is one or more selected from polycarbonate, polystyrene, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polypropylene, polyethylene, polyvinylidene chloride, polybenzimidazole, ethylene-vinyl acetate copolymer, polyimide, polyimide-triphenyl phosphate copolymer and polyurethane, preferably a composite current collector of aluminum and polyimide-triphenyl phosphate copolymer.
3. The negative electrode-free lithium metal battery according to claim 1, wherein: The positive electrode active material is one or more selected from ternary nickel cobalt lithium manganese oxide positive electrode material, lithium manganese-rich based positive electrode material, lithium nickel manganese oxygen positive electrode material, lithium iron phosphate positive electrode material, lithium manganese oxide positive electrode material, lithium iron manganese phosphate positive electrode material, lithium cobalt oxide positive electrode material and lithium sulfide positive electrode material, preferably a ternary nickel cobalt lithium manganese oxide positive electrode material.
4. The negative electrode-free lithium metal battery according to claim 1, wherein: The lithium-supplementing additive is one or more selected from binary lithium-containing compounds and lithium-rich compounds; the binary lithium-containing compound is one or more selected from Li2O, Li2O2, Li3N, Li2S and Li2C2O4, preferably Li2C2O4; the lithium-rich compound is selected from Li2Ni 1-x M x O2 or Li5Fe 1-x N x O4, wherein 0≤x<1, and M is at least one selected from Mn, Fe, Co, Cu, Zn, Mg, and Cd, and N is at least one selected from Mn, Ni, Co, Cu, Zn, Mg, and Cd. Preferably, the lithium supplement additive is one or both of Li2NiO2 and Li5FeO4.
5. The negative electrode-free lithium metal battery according to claim 1, wherein: The negative electrode current collector is selected from a metal current collector, a non-metal current collector or a metal-polymer composite current collector; Preferably, the metal current collector is an alloy of one or more selected from copper, nickel, cobalt, titanium and iron, preferably copper foil; the non-metallic current collector is one or more selected from carbon fiber cloth, carbon fiber paper, graphite paper and conductive organic polymer, preferably graphite paper; the polymer in the metal-polymer composite current collector is one or more selected from polycarbonate, polystyrene, polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polypropylene, polyethylene, polyvinylidene chloride, polybenzimidazole, ethylene-vinyl acetate copolymer, polyimide, polyimide-triphenyl phosphate copolymer and polyurethane, preferably a composite current collector of copper and polyimide-triphenyl phosphate copolymer.
6. The negative electrode-free lithium metal battery according to claim 5, wherein: The negative electrode current collector has a coating on at least one side, and the coating is selected from a metal coating, a non-metal coating or a metal-non-metal mixed coating; Preferably, the metal is one selected from indium, cobalt, germanium, aluminum, tin, gold, silver, zinc, magnesium, silicon, bismuth, palladium and platinum, or an alloy of two or more of the foregoing, and the non-metal is one or more selected from acetylene black, ketjen black, carbon black, graphite, graphene, conductive polymers and artificial interface films.
7. The negative electrode-free lithium metal battery according to claim 1, wherein: The boron-containing lithium salt is one or more selected from lithium difluorooxalatoborate, lithium dioxalatoborate, lithium tetrafluoroborate, lithium fluoroalkoxyborate, lithium fluoroalkoxyfluoroborate, lithium fluoroalkoxybisfluoroborate and lithium fluoroalkoxytrifluoroborate, preferably lithium difluorooxalatoborate; and / or The fluorinated amide compound is one or more selected from N,N-dimethyltrifluoroacetamide, N-methoxy-N-methyltrifluoroacetamide, N-methyltrifluoroacetamide, N,N-diethyltrifluoroacetamide, N-(trifluoromethanesulfonyl)trifluoroacetamide, N,O-bis(trimethylsilyl)trifluoroacetamide, N-methyl-N-(trimethylsilyl)trifluoroacetamide, bis(trimethylsilyl)trifluoroacetamide, N-methyltrimethylsilyltrifluoroacetamide, N-methylbis(trifluoroacetyl)amide, trifluoroacetamide and bistrifluoroacetamide, preferably N,N-dimethyltrifluoroacetamide; Preferably, the electrolyte comprises lithium difluorooxalatoborate and N,N-dimethyltrifluoroacetamide, and the molar ratio of lithium difluorooxalatoborate to N,N-dimethyltrifluoroacetamide is 1:
5.
8. The negative electrode-free lithium metal battery according to claim 1, wherein: The separator is selected from porous polyolefin polymer films or porous non-woven fabrics. Furthermore, at least one side of the diaphragm has a ceramic coating or a solid electrolyte coating.
9. The method for preparing a negative electrode-free lithium metal battery according to any one of claims 1 to 8, comprising the following steps: coating the composition for forming the positive electrode active material layer on the positive electrode current collector to thereby prepare the positive electrode; Mixing a composition for forming the electrolyte comprising at least one of the boron-containing lithium salt and a fluorinated amide compound solvent to thereby prepare the electrolyte; The positive electrode, the negative electrode current collector, the electrolyte and the separator are arranged to thereby prepare the negative electrode-free lithium metal battery.
10. Use of the negative electrode-free lithium metal battery according to any one of claims 1 to 8 in electronic devices, smart grids or electric vehicles.
Citation Information
Cited By
Positive active slurry of lithium ion battery, positive pole piece and lithium ion battery
CN120613383A
High-grain-boundary-strength LiCu3-cu composite current collector and preparation method and application thereof
CN122716342A